Insurgent - Roth, Veronica (NY : Katherine Tegen Books, 2012)
"As war surges in the dystopian society around her, sixteen-year-old Divergent Tris Prior must continue trying to save those she loves--and herself--while grappling with haunting questions of grief and forgiveness, identity and loyalty, politics and love"--
"Contains Free Four, a pivotal scene retold, faction tattoos, poster, and much more!"--Jacket..
Sequel to: Divergent.
Sequel: Allegiant.
Keywords: Identity -- Fiction; Families -- Fiction; Courage -- Fiction; Social classes -- Fiction; Science fiction